In Vitro Growth-Inhibitory Synergistic Effect of Zinc Pyrithione in Combination with Gentamicin against Bacterial Skin Pathogens of Livestock - Mala, Lucie; Lalouckova, Klara; Skrivanova, Eva; Houdkova, Marketa; Strakova, Marie; Kokoska, Ladislav (Antibiotics (Basel, Switzerland), 2022)
Bacterial skin diseases of livestock could be a serious global threat, especially in association with overcoming bacterial resistance. Combinatory action of antimicrobial agents proves to be an effective strategy to overcome the problem of increasing antibiotic resistance of microorganisms. In this study, the in vitro combined effect of zinc pyrithione with gentamicin against bacterial skin pathogens of livestock (Staphylococcus aureus, Streptococcus agalactiae, and Streptococcus dysgalactiae) was evaluated according to the sum of fractional inhibitory concentration indices (FICI) obtained by checkerboard method. The results showed that a combination of zinc pyrithione with gentamicin produced a strong synergistic effect (p < 0.001) against all tested streptococcal strains (with FICI values ranging from 0.20 to 0.42). Compared to that, only three out of eight S. aureus strains were highly susceptible to the combination of antimicrobial agents at single concentration (0.25 µg/mL) of zinc pyrithione with range of FICI 0.35−0.43. These findings suggest that interference between agents tested in this study can be used for the development of future veterinary pharmaceutical preparations for the treatment of bacterial skin infections of livestock.
Keywords: fractional inhibitory concentration; checkerboard microdilution method; antimicrobial interaction; gentamicin; zinc pyrithione